Organizational Routines, Complexity and Emerging Properties - Melo, Tatiana Massaroli de [UNESP] (Taylor & Francis, 2024)
The objective of this article is to relate the concepts of routines and emerging properties to understand how organizational processes, characterized by the use of similar routines, produce unforeseen and different results among firms. The analysis starts from the recognition that the organization is a complex structure, constructed of heterogeneous and adaptive parts that present relations of interdependence. Based on the interaction between these parties, it is possible to observe the emergence of behavior routines that are disseminated among other firms, making possible not only the reproduction of the organization, but also the generalization of these patterns for sectors of economic activity.
Keywords: complexity; coordination mechanisms; dynamic capabilities; routines